Analisis Padat Tebar Terhadap Pertumbuhan Dan Kelangsungan Hidup Ikan Nila (Oreochormis N Ilocitus) Di Kolam Buatan Laboratrium Basah Fakultas Perikanan, Universitas Lambung Mangkurat Menggunakan Metode Klaster Dan Pca (Principal Component Analysis) - Fionna Lelay Ariesalonika; Krisdianto Krisdianto (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
This study aims to analyze the effect of stocking density on the growth and survival of Tilapia (Oreochromis niloticus) in an artificial pond of the Wet Laboratory of the Faculty of Fisheries, Lambung Mangkurat University. The study was conducted for five weeks on nine maintenance plots with different stocking density variations, and each plot was observed periodically for fish weight and length growth. Data were analyzed using normality test, ANOVA test, Kruskal-Wallis test, and Friedman test, and strengthened with multivariate approach in the form of cluster analysis and Principal Component Analysis (PCA). The results showed that fish weight growth was significantly different between plots (p = 0.012), while length growth showed no significant difference (p = 0.316). Plot 5 showed the highest weight growth, while plot 1 recorded the lowest growth. Cluster analysis and PCA results grouped the plots based on similar performance, and identified Plot 5 as a positive outlier. This finding indicates that stocking density and feed treatment play an important role in fish weight growth, while length growth is more influenced by biological factors that tend to be stable. Therefore, fish weight is recommended as a key indicator in aquaculture management evaluation